2022
DOI: 10.1007/s40820-022-00907-4
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Anti-Proton Electrolyte for High-Rate and Super-Stable Aqueous Zn-Vanadium Oxide Battery

Abstract: Large volumetric expansion of cathode hosts and sluggish transport kinetics in the cathode–electrolyte interface, as well as dendrite growth and hydrogen evolution at Zn anode side are considered as the system problems that cause the electrochemical failure of aqueous Zn-vanadium oxide battery. In this work, a multifunctional anti-proton electrolyte was proposed to synchronously solve all those issues. Theoretical and experimental studies confirm that PEG 400 additive can regulate the Zn2+ solvation structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…As shown in Fig. 7 a, the diffraction peak of (003), (510) and (− 711) of VO 2 would shift toward a lower angel in the charge process, and recovery during the discharge process, which indicates the reversible insertion/extraction of zinc ion from VO 2 [ 44 ]. Note that the diffraction peak located at about 33° should be attributed to the formation of Zn 3 (OH) 2 V 2 O 7 ·2H 2 O by-product (PDF: 00-050-0570), which was generated in the discharge process and dissolved in the subsequent charge process [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 7 a, the diffraction peak of (003), (510) and (− 711) of VO 2 would shift toward a lower angel in the charge process, and recovery during the discharge process, which indicates the reversible insertion/extraction of zinc ion from VO 2 [ 44 ]. Note that the diffraction peak located at about 33° should be attributed to the formation of Zn 3 (OH) 2 V 2 O 7 ·2H 2 O by-product (PDF: 00-050-0570), which was generated in the discharge process and dissolved in the subsequent charge process [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inductive effect of alkyl groups in PEG as electrondonating groups and the stronger hydrogen bond interaction between H 2 O-PEG/OTf − with numerous functional groups helps to weaken the hydrogen bond between free water molecules, which undoubtedly strengthens the OH covalent bond and suppresses the parasitic reaction. [44][45][46] In addition, the incorporation of longchain molecules of PEG extends the electrochemical stability window of the electrolyte and inhibits the water decomposition (Figure S13, Supporting Informa tion). The overlapping profiles in cyclic voltammetry (CV) measurements reveal the highly reversible redox behaviors in Cu-Te cells with a hybrid electrolyte configuration as shown in Figure 5c, and exhibit a pair of redox peaks at 0.411/0.555 V (vs SHE, 0.07/0.22 V vs Cu/Cu 2+ ).…”
Section: Resultsmentioning
confidence: 99%
“…MD simulation has become a reliable tool for studying molecular and atomic systems under specific environmental conditions in computational work. From the perspective of dynamics, the evolutionary behavior of the system is studied by simulating the motion states of atoms and molecules within a certain time [ 106 , 107 , 108 ]. Inspired by host-guest interactions, Zhi et al reported a strategy for anion trapping in AZIBs.…”
Section: Theoretical Study On Modified Zinc Anodementioning
confidence: 99%